Legal Regulations Regarding the Placement of Medical Personnel on Domestic Civil Passenger Aircraft in Indonesia Reviewed from Law Number 1 of 2009 Concerning Aviation - Toha Achmad Saputra; Marjan Miharja (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Airplanes are one of the main choices of air transportation for Indonesian people. During the flight, passengers sometimes experience various health problems that require the assistance of medical personnel. This study aims to analyze the legal regulations for the placement of medical personnel on domestic civil passenger aircraft based on Law No. 1 of 2009 concerning Aviation at this time, and to analyze future legal regulations regarding the placement of medical personnel on domestic civil passenger aircraft in Indonesia. This research method is normative juridical, using a statutory regulatory approach. From the results of this study, the placement of medical personnel on domestic civil passenger aircraft in Indonesia has not been regulated in Law No. 1 of 2009 concerning Aviation. For future legal regulations, regarding the placement of medical personnel on domestic civil passenger aircraft in Indonesia, legal regulations must be immediately stipulated. These legal regulations can be added to Law No. 1 of 2009 concerning Aviation. The government, the Indonesian House of Representatives, airlines and related parties must immediately stipulate these legal regulations to fill the legal gap and provide legal certainty to medical personnel and airlines.